ANTIUROLITHIATIC ACTIVITY OF ACTIVITY OF TECOMA STANS LEAF EXTRACT (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Herbal medicines offer vast scope for the successful treatment of urolithiasis. Although most remedies were herbal and proved useful, a systematic scientific evaluation has been reported for only few remedies. Tecoma stans a herbal formulation was claimed to be useful in the treatment of urinary stones. Toxicity study confirms that the therapeutic dose of Tecoma stans was 430 mg/kg. The antilithiatic effect of Tecoma stans was determined on lactose diet + ethylene glycol induced and ammonium chloride + ethylene glycol induced lithiasis in male albino wistar rats. The results obtained after 4 weeks of treatment for the urine estimation of calcium, oxalate, magnesium and protein were significant (p